Rapid biomonitoring of heavy metals in polluted sites using Xenoassaya-metal - Rahman, Mohd Fadhil Abdul; Manogaran, Motharasan; Shukor, Mohd Yunus (Hibiscus Publisher, 2022)
Long-term water contamination, including heavy metals, may harm the reputation of the location. Because of this, it is necessary to do regular water quality checks. In light of the high expense of instrument monitoring, biomonitoring based on enzymes is rapidly gaining popularity around the world. For the purpose of this investigation, a molybdenum-reducing enzyme from the Serratia marcescens strain DRY6 that is sensitive to the heavy metals was used to build a quick inhibitory enzyme assay. The bacterium's molybdenum-reducing activity is extremely vulnerable to heavy metals. With the help of the established assay, heavy metals were detected in water samples collected in Malacca, Penang, and Perak. A number of sampling locations in Penang were found to be inhibiting enzyme activity, while all sampling locations in Malacca and Penang were confirmed to be free of high heavy metal concentrations. The Malaysian Department of Environment has set a maximum permissible limit for the suppression of Mo-reducing enzyme activity in Penang. Detection of heavy metals can be done in less than ten min at room temperature. The entire procedure takes less than 20 min. a first screening procedure or even a near real-time method for routine monitoring of heavy metals, assay is quick and straightforward